2016
DOI: 10.1080/02656736.2016.1247299
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy of three-dimensional (3D) visualisation operative treatment planning system and US-guided percutaneous microwave ablation in larger renal cell carcinomas (D ≥ 4 cm): preliminary results

Abstract: Materials and methods:The results from 20 patients with 20 larger RCCs treated with a 3D visualisation operative treatment planning system and US-guided PMWA were reviewed retrospectively. The patients were followed up by contrast-enhanced images at 1, 3, and 6 months and every 6 months thereafter. The outcomes of overall survival and local tumour progression rate were statistically analysed. Results: The median follow-up period was 26 months. The mean time of ablation for one tumour was 1.1 ± 0.3 sessions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…All studies had a retrospective study design. Eight studies were reported from Western countries ( 4 8 9 14 15 17 18 19 ) and five from Eastern countries ( 10 11 12 13 16 ). In nine studies, the mean tumor size was less than 3.0 cm ( 4 8 9 10 11 15 17 18 19 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies had a retrospective study design. Eight studies were reported from Western countries ( 4 8 9 14 15 17 18 19 ) and five from Eastern countries ( 10 11 12 13 16 ). In nine studies, the mean tumor size was less than 3.0 cm ( 4 8 9 10 11 15 17 18 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…For technical outcomes, six studies reported TSR ( 4 8 14 15 17 19 ) and 13 studies reported TER ( 4 8 9 10 11 12 13 14 15 16 17 18 19 ). For oncologic outcomes, 13 studies reported LRR ( 4 8 9 10 11 12 13 14 15 16 17 18 19 ), seven studies reported CSSR ( 8 10 12 13 14 17 18 ), and eight studies reported OSR ( 8 10 12 13 14 15 17 18 ). All 13 studies reported various major or minor complications post-MWA ( 4 8 9 10 11 12 13 14 15 16 17 18 19 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations